Influence of Antibiotic Contamination on Functioning of Microbiocenosis of Ordinary Chernozem - Akimenko, Yuliya Viktorovna (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: Wide-scale application of numerous antibiotics with various chemical compositions and spectra in medicine, agriculture, and food industry is accompanied by violation of microbial community in various ecosystems. Therefore, the resistance of microbial community of soils to contamination with antibiotics widely applied in medicine and agriculture (tylosin and oxytetracycline) has been assessed. Antibiotic contamination leads to decrease in the count of main ecotrophic groups of microorganisms, variation of their ratio, and structure of microbial community in total. Materials and Methods: Maximum impact of antibiotics was exposed in the 1st day after contamination of chernozem (3 days). Later (30 and 90 days), the trend of recovery of biological performances was observed, and dynamics of recovery of both microorganisms and enzyme activity was non-linear. Results: In terms of resistance to antibiotics, the considered microorganisms could be ranged as follows: Micromycetes >p. Azotobacter bacteria > amylolytic bacteria > ammonifiers. Comparison of laboratory and field simulation of antibiotic contamination of chernozem revealed that the rate of deterioration of biological performances was more pronounced under laboratory conditions in comparison with the field. Conclusion: The recovery rate of chernozem biological activity after field contamination was higher more than by 2 times. Probably, this could be attributed to the fact that in the field environment antibiotics were decomposed more rapidly under climatic impacts.